Estimating the dietary and health impact of implementing front-of-pack nutrition labeling in Canada: A macrosimulation modeling study - Flexner, Nadia; Ng, Alena P.; Ahmed, Mavra; Khandpur, Neha; Acton, Rachel B.; Lee, Jennifer J.; L’Abbe, Mary R. (Frontiers in Nutrition, 2023)
Front-of-pack labeling (FOPL) has been identified as a cost-effective policy to promote healthy diets. Health Canada has recently published FOPL regulations that will require food and beverages that meet or exceed set thresholds for sodium, sugars, or saturated fat to display a ‘high in’ symbol on the front of the package. Although a promising measure, its potential impact on dietary intakes and health have not yet been estimated in Canada. This study aims to estimate 1) the potential dietary impact of implementing a mandatory FOPL among Canadian adults; and 2) the number of diet-related noncommunicable disease (NCD) deaths that could be averted or delayed due to these estimated dietary changes. Baseline and counterfactual usual intakes of sodium, total sugars, saturated fats, and calories were estimated among Canadian adults (n=11,992) using both available days of 24h recalls from the 2015 Canadian Community Health Survey-Nutrition. The National Cancer Institute method was used to estimate usual intakes, and adjusted for age, sex, misreporting status, weekend/weekday, and sequence of recall. Estimated counterfactual dietary intakes were modeled from reductions observed in experimental and observational studies that examined changes in sodium, sugars, saturated fat, and calorie content of food purchases in the presence of a ‘high in’ FOPL (four counterfactual scenarios). The Preventable Risk Integrated ModEl was used to estimate potential health impacts. Estimated mean dietary reductions were between 31 and 212 mg/day of sodium, 2.3 and 8.7 g/day of total sugars, 0.8 and 3.7 g/day of saturated fats, and 16 and 59 kcal/day of calories. Between 2,183 (95% CI 2,008-2,361) and 8,907 (95% CI 8,095-9,667) deaths due to diet-related NCDs, mostly from cardiovascular diseases (~70%), could potentially be averted or delayed by implementing a ‘high in’ FOPL in Canada. This estimation represents between 2.4% and 9.6% of the total number of diet-related NCD deaths in Canada. Results suggest that implementing a FOPL could significantly reduce sodium, total sugar, and saturated fat intakes among Canadian adults and subsequently prevent or postpone a substantial number of diet-related NCD deaths in Canada. These results provide critical evidence to inform policy decisions related to implementing FOPL in Canada.